Deceptio dolosa (kan. 1098 KPK) w wyroku Roty Rzymskiej c. Erlebach z 4 października 2012 r. - Góralski, Wojciech (Ius Matrimoniale, 2014)
The Rotal Turnus c. Erlebach, after examining (in the second instance) the case regarding annulment of the marriage ob dolum, adjudicated it negatively (non constare de nullitate matrimonii) recognizing that the attribute of a disease called thalassemia minor which occurs only at one of the parties (at the respondent in this case) shall not consist the attribute, which may seriously disturb the matrimonial community, according to can. 1098 CIC. It would be the attribute only when both parties suffered from this disease. Special attention in this judgment shall be put to the raised issue regarding the confidence level at the perpetrator of the deceit as for existence (or not) of a particular attribute.